Chemical composition of the woods oil of Glyptostrobus pensilis (Staunton ex D. Don) K. Koch from Vietnam - Dai, Do Ngoc; Thai, Tran Huy (Academia Journal of Biology, 2012)
The wood oil of Glyptostrobus pensilis (Staunt.) K. Koch collected from Dak Lak province, Vietnam, in May 2008 was isolated by steam distillation to give oil yield 0.35% and analyzed by Capillary GC/MS. Forty-one components have been identified accounting more than 84.04% of the oil respectively. The major constituents of this oil appeared to be a-pinene (18.92%), limonene (23.89%), b-caryophyllene (6.13%), caryophyllene oxide (5.89%) and bornyl acetate (5.16%). Less predominant constituents included germacrene D (3.55%), b-elemene (2.48%), b-myrcene (2.19%), b-selinene (2.10%), b-pinene (1.19%), a-amorphene (1.17%) and camphene (1.14%).